Study Of The Semantic-Stylistic Features Of The SocioPolitical Lexican In "Starry Nights" And "General Treatment". - Rakhimov Abdukarim Akim ugli (Periodica Journal, 2024)
This study examines the semantic and stylistic features of sociopolitical vocabulary used in the literary works “Starry Nights” and “The Cure for Generations”. By examining the use of language in these texts, we aim to reveal how authors use socio-political vocabulary to convey deep meanings, evoke emotions, and engage readers in critical reflections on social problems. Through a comprehensive analysis of the selected works, this article highlights the importance of socio-political vocabulary in shaping thematic and stylistic elements of literature
Keywords: Literature; Starry Nights; Analysis